Microempresa familiar e empreendedorismo no Bairro São Pedro em Teresina - Pi - Nascimento, Isidro José Bezerra Maciel Fortaleza do (2008)
The process of globalization brings with it the competitiveness as one of the main features of market economies. Feeling that the development of entrepreneurial skills, more than ever becomes a constant need within the business. With regard to the characteristics micro entrepreneurs are proving as an important tool to gain in competitiveness, so for his stay in market. Starting from this scenario of the market as they aim of this study assess the presence of the characteristics of entrepreneurs in micro family neighborhood of São Pedro in municipality of Teresina in state of Piaui. The study makes a brief review of theories on the family business and, its relationship with entrepreneurship, and based their analysis on the theory of behavior entrepreneur, of David McClalland (1987), as well as in literature found. The type of research is exploratory, empirical, and descriptive. The information was obtained by direct search. The universe of search was constituted by 109 micro of the neighborhood São Pedro in Teresina, Piauí, identified by the survey conducted by us. Conclude that all the companies surveyed with more than 5 years existence, the theory of behavior enterprise of McClalland, demonstrating the validity of variables indicator of entrepreneurial behavior.